PERANCANGAN TYPEFACE UNTUK MENINGKATKAN CITRA BRAND RAWTYPE RIOT - Reza Gamas Firdansyah; Inko Sakti Dewanto (Jurnal Riset Multidisiplin Edukasi, 2025)
Visual identity plays a vital role in shaping brand image and competitiveness, especially in the highly dynamic fashion industry. Typography, particularly the font, functions not only as a medium of communication but also as a representation of the brand’s character and values. However, many local brands still rely on generic or pirated fonts, leading to weak differentiation, low credibility, and limited consumer engagement. This study focuses on developing an exclusive font for Rawtype Riot, a Bandung-based fashion brand, as a strategic effort to strengthen its visual identity. Using a qualitative approach, the research employed literature review, observation, in-depth interviews, and benchmarking, supported by a SWOT analysis to examine strengths, weaknesses, opportunities, and threats in custom font development. The findings indicate that Rawtype Riot’s consistency and progressive character create strong potential to pioneer custom typography within Indonesia’s local fashion industry, supported by Bandung’s creative ecosystem. The designed typeface, “Rawsome,” adopts a modern sans-serif style that is simple, solid, and dynamic, effectively reflecting the brand’s identity. The study concludes that exclusive font development enhances visual consistency, builds credibility, and fosters emotional connections with consumers. Moreover, it positions Rawtype Riot as a distinctive and professional brand, reinforcing originality while opening opportunities for broader recognition at both national and global levels.